Preliminary Study on Contextual Digital Book and AI Audio Media for English Learning in Vocational Culinary and Tourism Programs - Ismail; Rusdin; Andi Prayudi (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to identify the challenges and needs of students in learning English at SMKN 1 Hu'u Dompu, especially in the culinary and tourism programs. This study used a qualitative method with semi-structured interviews with two English teachers. The results showed that students faced difficulties in speaking, pronunciation, and low learning motivation due to irrelevant materials. This study suggests the development of English books specifically for culinary and tourism majors with an interactive and context-based approach, integration of local Dompu culture, and the use of digital technology such as digital books with AI-assisted audio to improve pronunciation skills. The combination of technology, local context, and relevant materials can create a more engaging and effective learning experience for students.